Pancreas transplant in type 1 diabetes mellitus: the emerging role of islet cell transplant - Inderpal Singh Kochar; Rakhi Jain (Korean Society of Pediatric Endocrinology, 2021)
Pancreas transplant, both whole pancreas and islet cell, is a known therapeutic option for treatment of type 1 diabetes mellitus. Islet cell transplant began as an experimental therapy but is emerging to be quite beneficial due to less surgical risk and fewer complications. It is also considered a promising option in pediatric patients. In this review the authors discuss the indications, procedure, and benefits of islet cell transplant along with newer strategies for improving outcomes.